Pragmatic Encroachment, Phenomenology, and Religious Experience - Michael D. Barber (Religions, 2022)
Aaron Rizzieri’s Pragmatic Encroachment, Religious Belief, andPractice (2013) is the fullest religious appropriation of a relatively new epistemological concept: pragmatic encroachment. To achieve this goal, Rizzieri rightly sees (1) how justification takes place within an encompassing pragmatic context and (2) how justification of religious belief establishes within a wider context less than absolute knowledge. While the first point can be supported by Alfred Schutz’s theory of action, often including multi-layered sub-acts, Schutz’s idea of a theoretical enclave can create a space for epistemic evidentialism, as an independent distinctive moment, with distinctive (justificatory) purposes, within an overarching practical action. Rizzieri’s book itself exemplifies such evidentialism, theoretically justifying pragmatic encroachment, after the fashion of Husserlian transcendental phenomenology. Rizzieri could also profit from Husserlian regional ontologies, on which he implicitly already relies to support religious knowledge. Husserl’s concept of bipolar intentionality would accommodate Rizzieri’s responsible internalism, while allowing for the action of objects upon us. This, in turn, opens the door to the evidence for religious knowledge that an account of religious experience such as Max Scheler’s could provide. Such an account could counter those who reduce religious experience to mere subjective projection—a critique to which internalism might be more vulnerable.